Effect of aperture number on pollen germination, survival and reproductive success in Arabidopsis thaliana. (18th January 2018) - Albert, Béatrice; Ressayre, Adrienne; Dillmann, Christine; Carlson, Ann L; Swanson, Robert J; Gouyon, Pierre-Henri; Dobritsa, Anna A
Abstract: Background and Aims: Pollen grains of flowering plants display a fascinating diversity of forms, including diverse patterns of apertures, the specialized areas on the pollen surface that commonly serve as the sites of pollen tube initiation and, therefore, might play a key role in reproduction. Although many aperture patterns exist in angiosperms, pollen with three apertures (triaperturate) constitutes the predominant pollen type found in eudicot species. The aim of this study was to explore whether having three apertures provides selective advantages over other aperture patterns in terms of pollen survival, germination and reproductive success, which could potentially explain the prevalence of triaperturate pollen among eudicots. Methods: The in vivo pollen germination, pollen tube growth, longevity and competitive ability to sire seeds were compared among pollen grains of Arabidopsis thaliana with different aperture numbers. For this, an arabidopsis pollen aperture series was used, which included the triaperturate wild type, as well as mutants without an aperture (inaperturate) and with more than three apertures. Key Results: Aperture number appears to influence pollen grain performance. In most germination and longevity experiments, the triaperturate and inaperturate pollen grains performed better than pollen with higher aperture numbers. In mixed pollinations, in which triaperturate and inaperturate pollen were forced to compete with each other, the triaperturate pollen outperformed the inaperturate pollen. Conclusions: Triaperturate pollen grains might provide the best trade-off among various pollen performance traits, thus explaining the prevalence of this morphological trait in the eudicot clade.